Analysis of Losses of propulsion systems on Electric Diesel Rail Trains - Jamal, Agus; Chamim, Anna Nur Nazilah; Putra, Karisma Trinanda; Masfiyah, Nisfi Nurlailatul; Jusman, Yessi (Universitas Muhammadiyah Yogyakarta, 2018)
Train is one of transportation which supports the mobilization of society. Futhermore, it is affordable and comfortable so that people prefer using it. One of trains which is usually used by many people is KRDE or electric diesel railway, which is an innovation of technology in PT. INKA based on railway industry. It is one of railway that need electricity as the main source of energy that comes from alternator. it will handle all power of load needs on KRDE like as propulsion and auxiliary load. Therefore, the fluency of KRDE is affected by electrical system of the railway, which is mostly affected by propulsion load because it needs bigger power than auxiliary load. In this research presents about losses calculation on KRDE that are Three- phase rectifier, Variable Voltage Variable Frequency (VVVF) inverter and Three phase induction motor. Three phase rectifier and VVVF inverter will simulated by PSIM software to understand how the circuit work. The results of this research are explain about the number of loss energy in three phase rectifier is 21,6 Watt. In VVVF inverter and three induction motor, there are five samples. From analysis of the samples result that VVVF inverter has the highest efficiency 95,53% with loss energy 19,992 KW, which on 645 Volt about output voltage and 90 Hz about output frequency. In three phase induction motor, 91, 426% is the highest efficiency and it has 18,211 KW at loss energy, which on 635 Volt about input voltage and 36,38 Hz about input frequency. Then, the highest efficiency of propulsion system is 94,59% and 53,38 KW about loss energy, which on 635 Volt about input voltage and 36,38 Hz about input frequency in induction motor.